POVERTY IN ANDREA HIRATA’S NOVEL ORANG ORANG BIASA - Satiman Satiman; Sri Chairani; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara, 2023)
This study aims to reveal poverty which is one of the social problems reflected in Andrea Hirata's novel Orang Orang Biasa. This research is considered important and feasible to do because it is an effort to convey social criticism to the government and related parties on poverty which is the most common social problem often faced by society. This research is a descriptive qualitative research and applies the sociological theory of literature put forward by Laurenseon and Swingewood (1972) to understand and evaluate literary works by considering social aspects. The finding of this study indicates various types of social problems in the novel stem from one problem, namely poverty, both material and moral poverty.